MANAJEMEN SUMBER DAYA MANUSIA DI PERPUSTAKAAN STIKI INDONESIA - Hermawan, I Gede Edi; Suhatika, I Putu; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2019)
ABSTRACT The purpose of this study was to find out and analyze human resource management at the STIKI Indonesia Library by using SWOT Analysis. The object of this research is HR management at the STIKI Library. This research is desc.riptive with a qualitativapproch. The techniqu of datacollection is done by interview,observation, documentation,andliteraturestudies. The results conducted by the authors indicate that HR management at the STIKI Indonesia Library is still not optimally done. It can be seen from the application of management functions that in terms of planning the library is only made based on the needs of the library. In managing existing human resources, the library has not fully implemented management functions, namely in terms of planning. In addition, the management functions are not based on the theories of management science, but are based on the needs and experiences in the library. Keywords: Management, HR Library, Library, SWOT Analysis